Opioid Prescription, Morbidity, and Mortality in US Transplant Recipients - Abbott, Kevin C. (Transplantation, 2018)
BACKGROUND: CDC guidelines recommend caution in prescribing opioids for chronic pain. The characteristics of opioid prescription (OpRx) among kidney transplant (KTx) recipients has not been described in a national population. METHODS: We assessed OpRx prevalence among prevalent KTx recipients, and associated duration (chronic, defined as ≥90 days in a year) and dosing (in morphine milligram equivalents per day, MME, of <50, 50–89, and ≥90) with outcomes, death and graft loss, among incident KTx recipients using 2006–2010 US Renal Data System files, including Medicare Part D for medication ascertainment. Cox models controlled for recipient factors. RESULTS: Of 36,486 KTx recipients in the 2010 prevalent cohort, approximately 14.6% had chronic OpRx. The strongest association with chronic OpRx after KTx was chronic OpRx before KTx (64%; adjusted odds ratio, 95% confidence interval [CI]: 95.2, 74.2–122.1). Incident KTx recipients with chronic OpRx had increased risk of mortality and graft loss compared with those without OpRx or short-term OpRx after KTx. This risk was highest among recipients with chronic OpRx doses of ≥90 MME (adjusted hazard ratio, 95% CI: 1.61, 1.24–2.10 for death, and 1.33, 1.05–1.67 for graft loss, respectively). CONCLUSIONS: In contrast to either no or short-term OpRx, chronic, and especially chronic high dose OpRx is associated with increased risk of death and graft loss in US KTx recipients. Causal relationships cannot be inferred, and OpRx may be an illness marker. Nevertheless, efforts to treat pain effectively in KTx recipients with less toxic interventions and decrease OpRx deserve consideration.